PAINTING AND COLOR-INTERDEPENDENT AFFILIATION AND IMPORTANCE: चित्रकला और रंग-परस्पर अन्योन्याश्रित सम्बद्धता एवं महत्व - Srivastava, Lakshmi (International Journal of Research -GRANTHAALAYAH, 2014)
Painting is the best among the arts, giving religion, meaning, work and salvation. And there is a supreme Mars in the house where it is revered. Painting in Chitra Sutra is said to be the best among all the arts. All the arts make our life beautiful and beautiful. Vatsyayana mentions sixty-four types of arts in the 'Kamasutra' text. In the Vidyasamuddeshya episode of Kamasutra, in the 64 works of Kama, "Alakhya" has also been counted by Vatsyayana, who is mentioned in the (3014-22) mantras of "Yajurveda". Our best and Sanskrit literature is very rich and incomparable. It has many references on arts and painting. All have many details of the painting. The painting is reflective of Indian religion, philosophy and culture. कलाओं में चित्रकला सबसे श्रेष्ठ है जो धर्म, अर्थ, काम और मोक्ष देने वाली है। और घर में परम मंगल होता है जहाँ इसकी प्रतिष्ठा की जाती है। चित्र सूत्र में चित्रकला को समस्त कलाओं में श्रेष्ठ कहा गया है। समस्त कलाएँ हमारे जीवन को सुन्दर और रसमय बनाती हैं। वात्सायायन ने ‘कामसूत्र’ ग्रन्थ में चैंसठ प्रकार की कलाओं का उल्लेख किया है। ‘‘कामसूत्र के विद्यासमुद्देष्य प्रकरण में काम की उपायभूत 64 कलाओं में ‘‘आलेख्य’’ की भी गणना वात्सायायन ने की है, जिनका उल्लेख ‘‘यजुर्वेद’’ के (3014-22) मंत्रों में है।’’ 1चित्रकला की गणना समस्त कलाओं में अतिश्रेष्ठ और उद्देश्य पूर्ण रूप से की जाती है हमारा संस्कृत साहित्य अति समृद्ध एवं अतुलनीय है। इसमें कलाओं और चित्रकला पर अनेकों उल्लेख हैं। सभी में चित्रकला के बहुतेरे विवरण हैं। चित्रकला भारतीय धर्म, दर्शन एवं संस्कृति को प्रतिबिम्बित करने वाली होती है।